The Effect of Red Chili Drying Techniques in Making Bangkok Powder Sauce on Sensory Quality and Total Dissolved Solids - Syalek, Muhammad; Sachriani, Sachriani; Ridawati, Ridawati (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The present study aims to analyze the effect of drying techniques for red chili peppers in the production of powdered Bangkok sauce on sensory quality and total soluble solids. The research was conducted at the Food Processing Laboratory, with the experimental period running from December 2024 to August 2025. The research method applied was experimental, employing sun-drying, oven-drying, and dehydrator techniques for the chili peppers. Sensory quality analysis results showed a significant effect on color when chili drying was done using a dehydrator (α=0.05), whereas no significant effect was detected for chili aroma, texture, spicy taste, sweetness, or chili seed grain attributes. Hypothesis testing for total soluble solids (TSS) using ANOVA indicated a significant difference in sugar content due to drying methods, with the dehydrator technique resulting in 20.23°Brix. Duncan’s analysis demonstrated that the dehydrator drying technique had a significantly greater effect compared to the other methods. Salt content analysis for TSS using ANOVA and Duncan also showed a significantly higher result for the dehydrator method, with 19.53°Brix. Overall, the dehydrator drying technique produced the best quality results.